Nonsyndromic Intestinal Lipomas are Probably not Associated With Mutations of PDGFRA - Dubova, Magdalena; Sedivcova, Monika; Saskova, Bohuslava; Hadravska, Sarka; Daum, Ondrej (Applied immunohistochemistry & molecular morphology, 2017)
The purpose of this study was to test the hypothesis that intestinal lipomas occurring in patients devoid of signs of PDGFRA-mutant syndrome might represent sporadic counterparts of familial lipomatous tumors occurring in the spectrum of tumors associated with PDGFRA mutations. PDGFRA-mutant syndrome may manifest with gastrointestinal stromal tumors, Vanek tumors, fibrous tumors, and lipomatous tumors. Until now there has been no molecular genetic study of PDGFRA mutations in intestinal lipomas published in the world literature. A series of 20 intestinal lipomas were obtained from 17 patients, and mutational analysis of exons 12, 14, and 18 of the PDGFRA gene was performed. None of the 16 analyzable tumors showed mutations in PDGFRA. Thus, PDGFRA mutations probably do not play an important role in the development of sporadic lipomas of the intestines.
Keywords: mutace; exony; Exons; Humans; Mutation; Receptor, Platelet-Derived Growth Factor alpha; lipom; lidé; střevní nádory; růstový faktor odvozený z trombocytů - receptor alfa; Intestinal Neoplasms; Lipoma